Subdural Hematoma in Chronic Myelocytic Leukaemia - Pinzon, Rizaldy Taslim; Fedora, Gusti Ayu Jacinda Amanda (Jurnal Ilmu Kedokteran, 2025)
Chronic subdural hematoma is an old collection of blood between the arachnoid and dura mater that covers the brain surface. This condition is a common neurological emergency and commonly caused by craniocerebral trauma. Chronic subdural hematoma caused by leukaemia was rarely reported, and its pathogenesis and strategies for clinical treatment remain controversial. We report a rare case of chronic subdural hematoma caused by chronic myelocytic leukaemia (CML) in blast crisis. The patient was diagnosed as CML 8 months ago after ischemic stroke. The bone marrow cytology, flow cytology, and haematology consultation suggested chronic myelocytic leukaemia. The patient admitted again with headache and right side weakness. The routine blood examination showed blast crisis. The emergency neurosurgical consultation was performed, but the patient's condition deteriorated quickly after admission. The platelet levels continued to decrease after admission. In this case, early diagnosis and multidisciplinary treatment are important to minimalized the outcome and poor prognosis.